2020
DOI: 10.1242/jeb.213975
|View full text |Cite
|
Sign up to set email alerts
|

The ghost of temperature past: interactive effects of previous and current thermal conditions on gene expression in Manduca sexta

Abstract: High temperatures can negatively impact the performance and survival of organisms, particularly ectotherms. While an organism's response to high temperature stress clearly depends on current thermal conditions, its response may also be affected by the temporal pattern and duration of past temperature exposures. We used RNA sequencing of Manduca sexta larvae fat body tissue to evaluate how diurnal temperature fluctuations during development affected gene expression both independently and in conjunction with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…In contrast, patterns of HSP gene expression in response to heat shocks are similar in the two populations (Alston et al, 2020).…”
Section: Life-history Responses To Mean and Fluctuating Temperaturesmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, patterns of HSP gene expression in response to heat shocks are similar in the two populations (Alston et al, 2020).…”
Section: Life-history Responses To Mean and Fluctuating Temperaturesmentioning
confidence: 81%
“…This is consistent with the finding that larval survival at high, constant temperatures (35°C) is lower in the laboratory than the field population (Kingsolver & Nagle, 2007). In contrast, patterns of HSP gene expression in response to heat shocks are similar in the two populations (Alston et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this system, a lethal threshold for one interacting organism (the parasitoid wasp) triggers a different developmental outcome for another organism (the caterpillar). This concept relates back to individual variability when considering research regarding thermal acclimation and tolerance, where previous thermal history can change individual responses to stressful temperatures (Alston et al., 2020; Kingsolver et al., 2015; Marshall & Sinclair, 2012; Sinclair et al., 2003). While all caterpillars in this study experienced the same thermal conditions within treatment groups, the caterpillars' parental identity is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the black weed barrier treatment significantly increased the daily maximum T op seen in the middle of the tobacco plants when compared to the gray weed barrier treatment (post hoc Student's t test, t = −2.831, df = 209.73, p = 0.0051; Figure 1B; Appendix S2: Table S1 and Figure S6A,D). T op in the middle of the plant was consistently 1 C-3 C higher in the black weed barrier treatment than the gray (Figure 1B), a difference that can have important sublethal effects at high temperatures (Alston et al, 2020;Kingsolver et al, 2015;Ma et al, 2018). By contrast, daily minimum temperatures were similar in the two treatments, because of the lack of solar radiative heat differences during the night (LM, F 1,416 = 0.03, p = 0.8677; Figure 1D-F; Appendix S2: Table S1 and Figure S6B,E).…”
Section: Field Temperature Measurementsmentioning
confidence: 95%
“…Of particular interest to thermal biologists in recent years are the sublethal effects of high temperatures. For ectothermic organisms, even short exposures to temperatures near their upper thermal limit can have cascading physiological effects such as reduced feeding and growth, reduced movement, reduced fecundity, upregulation of heat shock proteins, and more (Alston et al, 2020; Kingsolver et al, 2015; Ma et al, 2018). If hosts and parasites differ in their thermal sensitivity or tolerance, increasing temperatures can change the dynamics or even the outcomes of species interactions (Furlong & Zalucki, 2017; Schreven et al, 2017).…”
Section: Introductionmentioning
confidence: 99%